2020
DOI: 10.1038/s41598-020-78692-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of PTEN in osteocytes increases circulating phosphate concentrations by decreasing intact fibroblast growth factor 23 levels

Abstract: Fibroblast growth factor 23 (FGF23) has been centric to the regulation of phosphate (Pi) metabolism; however, the regulatory network of FGF23 in osteocytes has not yet been defined in detail. We herein investigated the role of PTEN (phosphatase and tensin homolog deleted from chromosome 10) in this regulation. We created mice lacking PTEN expression mainly in osteocytes by crossing Pten-flox mice with Dmp1-Cre mice. The lack of PTEN in the osteocytes of these mice was associated with decreased skeletal and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…To further confirm that osteocytes respond to insulin to regulate FGF23 production, we generated mice with an osteocyte-specific deletion of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), a molecule that antagonizes insulin/IGF-1-induced AKT activation. These mice exhibit decreased skeletal and serum levels of intact FGF23, reduced urinary Pi excretion, and elevated serum Pi levels ( 94 ). Our in vitro studies suggest the involvement of the AKT/mechanistic target of rapamycin complex 1 (mTORC1) in insulin/IGF-1-induced suppression of FGF23 ( 94 ).…”
Section: Regulators Of Fgf23mentioning
confidence: 99%
“…To further confirm that osteocytes respond to insulin to regulate FGF23 production, we generated mice with an osteocyte-specific deletion of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), a molecule that antagonizes insulin/IGF-1-induced AKT activation. These mice exhibit decreased skeletal and serum levels of intact FGF23, reduced urinary Pi excretion, and elevated serum Pi levels ( 94 ). Our in vitro studies suggest the involvement of the AKT/mechanistic target of rapamycin complex 1 (mTORC1) in insulin/IGF-1-induced suppression of FGF23 ( 94 ).…”
Section: Regulators Of Fgf23mentioning
confidence: 99%
“…Furthermore, in the cultured osteoblastic cell line UMR106, insulin and insulin-like growth factor 1 (IGF-1) reduced the production of FGF23 by inhibiting forkhead box protein 1 (FOXO1) through the activation of the phosphoinositide 3-kinase/AKT pathway [120]. On the other hand, we recently reported that the production of FGF23 was reduced in mice with the osteocytespecific deletion of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), which decreased the renal excretion of Pi and increased serum Pi levels [134]. Furthermore, the knockdown of PTEN expression in UMR106 cells activated AKT/mechanistic target of rapamycin complex 1 (mTORC1), which reduced the expression of Fgf23 [134].…”
Section: Systemic Regulators Of Fgf23mentioning
confidence: 99%
“…On the other hand, we recently reported that the production of FGF23 was reduced in mice with the osteocytespecific deletion of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), which decreased the renal excretion of Pi and increased serum Pi levels [134]. Furthermore, the knockdown of PTEN expression in UMR106 cells activated AKT/mechanistic target of rapamycin complex 1 (mTORC1), which reduced the expression of Fgf23 [134]. These findings suggest that the insulin-and IGF1-induced activation of AKT inhibited the production of FGF23 through the FOXO1 and mTORC1 pathways.…”
Section: Systemic Regulators Of Fgf23mentioning
confidence: 99%
“…A treatment of the cultured osteoblastic cell line UMR106 with insulin and insulin-like growth factor 1 (IGF-1) also suppressed the production of FGF23 through the activation of the AKT pathway and the inhibition of forkhead box protein 1 (FOXO1) (52). We recently reported that the osteocyte-specific deletion of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), the molecule that antagonizes the insulin-induced activation of AKT, resulted in a decrease in the production of FGF23 in osteocytes, a reduction in renal phosphate excretion, and the attenuation of hyperphosphatemia (53). The knockdown of PTEN expression in UMR1-6 cells decreased the expression of Fgf23, which was partially restored by a treatment with rapamycin, suggesting the involvement of AKT/mechanistic target of rapamycin complex 1 (mTORC1) (53).…”
Section: Systemic Regulators Of Fgf23 Production In Osteocytesmentioning
confidence: 99%
“…We recently reported that the osteocyte-specific deletion of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), the molecule that antagonizes the insulin-induced activation of AKT, resulted in a decrease in the production of FGF23 in osteocytes, a reduction in renal phosphate excretion, and the attenuation of hyperphosphatemia (53). The knockdown of PTEN expression in UMR1-6 cells decreased the expression of Fgf23, which was partially restored by a treatment with rapamycin, suggesting the involvement of AKT/mechanistic target of rapamycin complex 1 (mTORC1) (53). These findings suggest that the insulin-and IGF1-induced activation of AKT in osteocytes inhibit the production of FGF23 through the FOXO1 and mTORC1 pathways.…”
Section: Systemic Regulators Of Fgf23 Production In Osteocytesmentioning
confidence: 99%